Analisis Efektivitas, Kontribusi, Efisiensi dan Elastisitas Penerimaan Pajak Provinsi Kalimantan Selatan Terhadap Pendapatan Asli Daerah (PAD) Provinsi Kalimantan Selatan - Saesaria, Nanarita Dwi Putri; Muhammad Saleh (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2025)
This research analyzes the Effectiveness, Contribution, Efficiency and Elasticity of South Kalimantan Province Tax Revenue on South Kalimantan Province's Original Regional Income (PAD) during 2018 – 2022. This research only focuses on seven types of regional taxes, namely Motor Vehicle Tax, Vehicle Title Transfer Fees Motorbikes, Heavy Equipment Tax, Motor Vehicle Fuel Tax, Surface Water Tax, Cigarette Tax and Opsen Tax on Non-Metal Minerals and Rocks. The method used is a quantitative descriptive analysis technique. The results of this research are that the level of regional tax effectiveness only in 2020 was classified as less effective, while in 2018, 2019, 2021 and 2022 it was categorized as effective. Regional tax efficiency during 2018 – 2022 is categorized as efficient. Regional tax contributions varied very well during the observation year. Regional tax elasticity in 2019 and 2021 is inelastic, while in 2018, 2020 and 2022 it is elastic.